Disease-activity-free status in patients with relapsing–remitting multiple sclerosis treated with daclizumab high-yield process in the SELECT study. (April 2014) - Havrdova, Eva; Giovannoni, Gavin; Stefoski, Dusan; Forster, Samantha; Umans, Kimberly; Mehta, Lahar; Greenberg, Steven; Elkins, Jacob
Background: Daclizumab high-yield process (DAC HYP) is a humanized anti-CD25 monoclonal antibody that inhibits high-affinity interleukin-2 receptor signaling. Objective: The objective of this paper is to assess the proportion of DAC HYP- versus placebo-treated patients who were free from disease activity. Methods: SELECT was a randomized, double-blind, multicenter study of DAC HYP 150 mg or 300 mg, or placebo, administered subcutaneously every four weeks for 52 weeks. In this post-hoc analysis of the SELECT trial, 'disease-activity free' was defined as completion through week 52 without relapses or confirmed three-month disability progression (clinical), with no new/newly enlarging T2-hyperintense lesions and no new gadolinium-enhancing lesions at the week 52 scan (radiological). Primary analyses were based on logistic regression controlling for baseline characteristics. Results: More DAC HYP-treated (39%, n = 156) versus placebo-treated patients (11%, n = 22) were disease-activity free (odds ratio (95% confidence interval), 6.18 (3.71–10.32); p < 0.0001). Furthermore, 77% and 48% of DAC HYP-treated patients were free from clinical or radiological disease activity, respectively, compared with 60% and 18% of placebo-treated patients. Conclusion: At one year, DAC HYP resulted in a meaningful increase in the proportion of relapsing–remitting MS patients who were disease-activity free versus placebo.